Institutional and individual factors associated with hepatitis B virus vaccination among newborns in the hospitals of Lima – Peru - Borda-Olivas, Alfredo (2023)
Introduction. Vaccination against hepatitis B Virus (HBV) in newborns is crucial for the prevention of perinatal transmission. Objective. To determine the individual and institutional factors associated with vaccine for HBV in newborns in the first 12 hours and 24 hours of life. Methods. A cross-sectional, multicenter-design study was conducted in high level public and private hospitals in Lima Metropolitana and Callao. Information on vaccination was obtained through consultations with parents and review of health service reports. Individual variables of the newborns and their mothers were obtained from the medical records of the newborns. Institutional data were collected from immediate care records and from health personnel responsible for the immunization program. Results. The study was conducted in 10 health facilities, including 777 newborns. In the multilevel analysis, the longest care time in the vaccination service was favorable for vaccination within 12 hours of life (PR: 1,0; 95% CI: 0,9995-1,01); while for vaccination within 24 hours of life was favorable the greater number of nursing personnel (RP: 1,02; IC95%: 1,01-1,03) and unfavorable the greater number of deliveries per day in the institution (RP: 0,99; IC95%: 0,99-0,997). No individual factors related to vaccination were identified. Conclusions. Institutional factors, such as length of care, number of nursing staff, and number of deliveries, were associated with newborn HBV vaccination. Improvement strategies are required, such as the introduction of vaccination in the immediate care of the newborn for the prevention of perinatal transmission of HBV.